IT Capital, Job Content and Educational Attainment - Alexandra Spitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Based on a large data set containing information on occupations between 1979 and 1999, this study explores the ?black box? surrounding the skill?biased technological change hypothesis by analyzing the mechanisms that induce information technologies to be complementary to employees with higher skill levels. Using direct, multidimensional measures of occupational skill requirements, the analysis shows that IT capital substitutes repetitive manual and repetitive cognitive skills, whereas it complements analytical and interactive skills. These changes in the within occupational task mix result in an increased deployment of employees with high levels of education who have comparative advantages in performing non?repetitive cognitive tasks.
Keywords: O30; J23; J24; C30; 330; skill-biased technological change; job task content; vocational education; Informationstechnik; Qualifikation; Technischer Fortschritt; Anforderungsprofil; Bildungsniveau; Hochqualifizierte Arbeitskräfte; Schätzung; Deutschland